PENDAMPINGAN PENINGKATAN USAHA KELOMPOK PETERNAK BABI DI WILAYAH GUNUNG NONA KOTA AMBON - Tatipikalawan, Jomima Martha; Matatula, Michel J.; Tomatala, George S. J. (Universitas Pattimura, 2025)
Community-Based Service Activities (PBM) – the Lecturer Community Service Program (PDM) aims to increase the income of pig farmers in the Gunung Nona area, Ambon City, through the formation of farmer groups and the development of product marketing. The activities were carried out by the PDM-PBM Team of Pattimura University using methods such as lectures, discussions, demonstrations, and participatory mentoring over two days. Participants consisted of small-scale farmers who have been running their businesses individually. The training materials included group management, partnership networks, product promotion, and technical management of animal care. Evaluation results showed a significant increase in farmers' knowledge and skills, from 31.27% and 44.23% to 82.38% and 91.67%, respectively. Partner farmers showed high responsiveness through active participation and numerous questions during the activities. A tangible impact of this activity is the formation of the Gunung Nona pig farmers group as an institutionally recognized organization, which is beginning to design collective marketing strategies. The establishment of the group and the strengthening of marketing capacity are expected to increase business efficiency, strengthen the bargaining position of the farmers, and open opportunities for sustainable income growth.